Effect of Citrus aurantifolia swingle essential oils on methyl mercaptan production of Porphyromonas gingivalis - Anindya Prima Yusinta; Ivan Arie Wahyudi; Anne Handrini Dewi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Halitosis is a term used to describe an unpleasant odors emanating timely from oral cavity. The unpleasant smell of breath most common caused from volatile sulphure compound (VSC). Methyl mercaptan is the major component of VSC. P. gingivalis produced large amount of methyl mercaptan. The essential oils of Citrus aurantifolia swingle contain antibacterial component. Purpose: The purpose of this study was to determine the effect of essential oil of Citrus aurantifolia swingle on the production of methyl mercaptan compounds in P. gingivalis. Methods: Bacterial suspension of P. gingivalis in TSB medium with 108 CFU/ml concentration cultured in a microplate and added by the essential oils of Citrus aurantifolia swingle with 1%, 2%, 3% and 4% concentration. Distilled water was used as negative control and 0.2% Chlorhexidine mouthwash was used as a positive control. Microplate was incubated anaerobically for 48 hours. After the periode of incubation, 0.6% methionine as the exogenous substrate and 0.06% DTNB as a reagen for determining methyl mercaptan concentration were added to each wells. The microplate was futher incubated for 12 hours. Concentration of methyl mercaptan produced by the P. gingivalis was measured spectrophotometrically using microplate reader at 415 nm. Results: One-way ANOVA showed that the essential oil of Citrus aurantifolia swingle take effect on the concentration of methyl mercaptan produced by P. gingivalis. LSD test results indicated that there was a significant difference of methyl mercaptan concentration between treatment groups of the essential oils of Citrus aurantifolia swingle and distilled water that used as negative control. Conclusion: The essential oil of Citrus aurantifolia swingle has decreased the production of methyl mercaptan produced by P. gingivalis.Latar belakang: Halitosis adalah istilah yang digunakan untuk menggambarkan bau tidak sedap yang berasal dari rongga mulut. Penyebab utama halitosis adalah senyawa volatile sulphur compound (VSC) dan metil merkaptan merupakan komponen VSC yang paling dominan menyebabkan halitosis. P. gingivalis dapat memproduksi metil merkaptan dalam jumlah banyak. Minyak atsiri kulit jeruk nipis (Citrus aurantifolia swingle) memiliki kandungan antibakteri di dalamnya. Tujuan: Untuk mengetahui pengaruh minyak atsiri kulit jeruk nipis terhadap produksi senyawa metil merkaptan pada bakteri P. gingivalis. Metode: Suspensi bakteri P. gingivalis dalam media TSB dengan konsentrasi 108 CFU/ml dibiakkan dalam microplate. Selanjutnya dilakukan penambahan minyak atsiri kulit jeruk nipis konsentrasi 1%, 2%, 3%, dan 4%. Obat kumur chlorhexidine 0,2% digunakan sebagai kontrol positif dan akuades sebagai kontrol negatif. Microplate diinkubasi selama 48 jam untuk selanjutnya dilakukan penambahan metionin 0,6% dan DTNB 0,06% dan diinkubasi kembali selama 12 jam. Konsentrasi senyawa metil merkaptan yang diproduksi oleh bakteri P. gingivalis dihitung dengan menggunakan microplate reader pada panjang gelombang 415 nm. Hasil: ANOVA satu jalur menunjukkan bahwa minyak atsiri kulit jeruk nipis berpengaruh terhadap konsentrasi metil merkaptan yang diproduksi oleh bakteri P. gingivalis. Hasil uji LSD menunjukkan adanya perbedaan yang signifikan antara kelompok perlakuan minyak atsiri kulit jeruk nipis dengan akuades sebagai kontrol negatif. Kesimpulan: Minyak atsiri kulit jeruk nipis dapat menurunkan produksi senyawa metil merkaptan yang dihasilkan oleh bakteri penyebab halitosis P. gingivalis.